NARASI APOKALIPTIK DALAM SASTRA EKOLOGIS: KAJIAN EKOKRITIK PADA CERPEN NATURA DAN ANAK MANUSIA KARYA ISTIFARA SUCI TAUFIKA - Akhmad Idris (TELAGA BAHASA, 2021)
Literary criticism with environmental insight has indeed begun to be taken into account recently, because previously literature was still viewed from the perspective of humans as social beings, not as biological beings. This study aims to explain apocalyptic narratives in short story “Natura dan Anak Manusia” and to determine the feasibility of short story “Natura dan Anak Manusia” as ecocritical literary works. The results of this study indicate that the short story “Natura dan Anak Manusia” by Istifara Suci Taufika meet the standards of apocalyptic narrative, so they can be called ecocritical literary works.Keywords: Apocalyptic Narrative, Natura dan Anak Manusia, dan Ecocritic